Social support and resilience among mothers of children with autism spectrum disorder: The moderating role of social support satisfaction - İbrahim Güngör; Gizem Yağmur Değirmenci; Özcan Doğan (Anatolian Journal of Health Research, 2026)
Aim: This study examines the moderating role of satisfaction with social support in the relationship between perceived social support and resilience among mothers of children with autism spectrum disorder (ASD). Methods: This study employed a cross-sectional survey model with a predictive correlational design. The study sample consisted of 107 mothers of children with ASD aged 6–18. Of these children, 73.8% were boys and 26.2% were girls. The data collected for the study were gathered using the Maternal Resilience Scale and the Revised Parental Social Support Scale. Results: The mediation analyses revealed that satisfaction with perceived social support significantly mediated the relationship between perceived social support and resilience (Est. = 0.0069, SE = 0.0032, Z = 2.14, p